Purificação e caracterização bioquímica da moozincina, uma metaloprotease dependente de zinco presente na peçonha da serpente Bothrops moojeni (Caiçaca) - Fonseca, Kelly Cortes (2010)
Bothrops snake venoms contain proteases that contribute to the local effects seen after envenoming. In this study, a non-hemorrhagic metalloprotease was isolated from the venom of B. moojeni. The enzyme was isolated by a combination of ion exchange and gel filtration chromatographies and named Moozincin. The enzyme was purified to homogeneity as judged by its migration profile in SDS PAGE stained with coomassie blue, and showed a molecular mass of about 30 kDa. Moozincin did not induce hemorrhage, blood clotting, defibrinating or phospholipase A2 activities, but displayed proteolytic activity on bovine fibrinogen. Moozincin cleaves the Aα-chain of fibrinogen first, followed by the Bβ-chain, and shows no effects on the γ-chain. The fibrinogenolytic activity of Moozincin was abolished after incubation with a chelating agent (EDTA, 1,10-phenantroline) β-mercaptoethanol, indicating that it is metal iondependent. In contrast, aprotinin and benzamidine did not affect these activities. Moozincin was active at pH 7 - 11 and was stable in solution at up to 50 °C; fibrinogenolytic activity was completely lost at ≥60 °C. Histological observations showed that Moozincin induces low myonecrosis upon intramuscular injection in mice evidenced by hyaline degeneration and leukocyte infiltrate. Moozincin induced cell alterations in lung, but not alter liver, kidney and heart cells.